GST fraud prevention to ensure business sustainability: a Malaysian case study. Issue 3 (27th July 2020) - Othman, Zaleha; Nordin, Mohd Fareez Fahmy; Sadiq, Muhammad
Abstract : Purpose: This study provides in-depth explanation of Goods and Services Tax (GST) fraud prevention towards sustainability business. Design/methodology/approach: This study applies a qualitative research method, i.e. case study, to address the specific research objective. Findings: The finding revealed a GST prevention model towards sustainable business. The finding shows that it is pertinent for the government to set preventive strategies in order to retain sustainable income for the government. Two essential dimensions emerged in the findings to support preventive strategies, namely macro- and micro-level measures. Practical implications: The findings of this study provide managers, investors and policymakers with evidence to what extent GST fraud could be minimize in order to safeguard government source of revenue and retain sustainable business in a country. As GST is an important source of revenue for the government, it is thus crucial to prevent fraud from occurring. Originality/value: Past studies have primarily focused on GST implementation from the perspective of service tax effectiveness and efficiency. However, this study examined the impact of GST fraud to determine measures that could ensure service tax sustainability using preventive strategies, in turn, introducing to the existing literature on indirect tax.